Newton versus Leibniz: uma luz sobre a controvérsia intelectual na descoberta do cálculo - Santos, Ronaldo Alberto Lima dos (Universidade Federal de São Carlos, 2023)
The purpose of this dissertation is to conduct a bibliographical research on the life and works of two of the greatest mathematical scientists of the 17th century, Isaac Newton and Gottfried Wilhelm Leibniz. Although the mathematicians had a vast intelectual repertoire, the research focuses on the aspects of their works and the historical consequences of their contributions. It was possible to observe that the vast amount of knowledge possessed by these scientists led Newon and Leibniz to clash over the priority of the Discovery of Calculus, garnering supporters na creating adversaries. This dispute resulted in a certain nationalism and had repercussions for Mathematics, such as a significant stagnation in the advancement of knowledge production. This dissertation presentes the controversial Search to determine who initially developed Differential and Integral Calculus, showcasing the versions that emerged at the time and continue to be debated to this day. However, it is not the aim of this dissertation to determine the first discoerer of Calculus; instead, it seeks to highlight the historical facts that contribute to Newton’s or Leibniz’s discoveries and their significance for Mathematics. It becomes evidente that each of them arrived at the development of their ideas differently, and both were instrumental in enabling Calculus to sole problems across various fields.
Newton versus Leibniz: a light on the intellectual controversy in the discovery of calculus
Keywords: Isaac Newton; Gottfried Wilhelm Leibniz; Descoberta do Cálculo; Discovery of Calculus; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO